(untitled) (Journal of Dhaka Medical College, 2025)
Background: Febrile seizure is a common pediatric emergency. This is the most common type of seizure in children aged 6 months to 6 years constituting 30% of all seizure types. Despite the high clinical burden of febrile seizure, little advance has been made in understanding its etiology. This study was undertaken to find out whether low serum zinc level is a risk factor of febrile seizure in children. Methodology: This case-control study was conducted in department of Pediatrics, Dhaka Medical College Hospital, Dhaka from March, 2021 to February, 2022. Sixty-nine children presenting with febrile seizure, fulfilling inclusion criteria were enrolled as cases, along with similar number (sixty-nine) of age and sex matched healthy controls. Venous blood samples were obtained and analyses of serum zinc levels were done. Results: The results of cases and controls were compared. Data were analyzed through SPSS (version 26) software. Significance for the statistical tests (Chi Square test & unpaired t-test) were determined at a probability value of less than 0.05 (p<0.05). Mean age of the respondents was 21.53±11.52 months in case group and 24.33±16.80 months in control group. Majority (59 to 62%) patients were male in both groups and majority (95.65%) of cases were simple febrile seizure and mean duration of seizure was 10.46±5.60 minutes. The mean serum zinc was found 76.84±14.16 µg/dl in case group and 81.59±13.28 µg/dl in control group. The difference between the case and control group was significant (P value = 0.044). ROC curve showed OR= 2.21, cut off value =84.5 (<65 µg/dl), p = 0.045, 95% CI, sensitivity = 71.0%, Specificity = 50.0%. Conclusion: Serum zinc was found to be significantly low in children with febrile seizure than that of febrile children without seizure. However further large-scale studies are needed to generalize the result of this study. J Dhaka Med Coll. 2024; 33(2) : 49-55